Anti atherosclerosis effect and mechanism of a novel curcumin analogue CACN136: regulating macrophage M1/M2 polarization and lipid metabolism - Zhao, Qianjiao; Zhong, Yueting; Li, Zheng; Tang, Jia; Pi, Chao; Zheng, Wenwu; Shi, Peng; Zuo, Ying; Jiang, Jun; Yang, Yan; Chu, Shifeng; Wei, Yumeng; et al. (Frontiers in Pharmacology, 2025)
IntroductionCurcumin has been found to inhibit atherosclerosis. However, its poor stability and low activity severely limit its further application. To overcome the shortcomings of curcumin, our team successfully designed a novel curcumin analog, CACN136. This study aims to explore the anti-atherosclerosis effects of CACN136 and its mechanisms.Method and ResultOil Red O staining results showed that CACN136 significantly improved atherosclerosis plaques in the aorta and aortic root of ApoE-/- mice. RNA sequencing analysis (RNA-seq) indicated that CACN136 inhibits atherosclerosis by regulating lipid metabolism and inflammation-related pathways. In vitro, CACN136 significantly upregulates the mRNA and protein expression of iNOS and Arg1 in LPS-induced RAW264.7 cells. In ox-LDL-induced RAW264.7 foam cells, CACN136 significantly reduced free cholesterol and total cholesterol levels, and the levels of ABCA1, CD36, and SRA1 mRNA and protein were significantly altered. In vivo, CACN136 significantly reduced lipid and inflammatory levels, with superior safety and efficacy compared to the same dose of simvastatin.DiscussionCACN136 improves atherosclerotic plaque by regulating macrophage polarization and lipid metabolism, suggesting that CACN136 may be a promising new drug for the treatment of atherosclerosis.